Solid-state synthesis of novel anticancer drug eutectic mixture; anticancer, physical and thermal studies - Chaudhary S.; Rai R.N.; Maity S.; Maiti P. (My University, 2025)
Green, solvent-free synthesis is adopted for a new pharmaceutical drug-drug eutectic with the utmost 100% yield. The synthesized eutectic mixture is significant for anticancer activity. The mandate of clinical tests could be avoided as selected nicotinamide, salicylamide, p-aminoacetinilide and benzanilide are known drugs. The compositional behaviors and established phase diagrams infer the formation of eutectics. The thermal behaviors of eutectics are studied using DSC. Further studies of eutectics are targeted for their biological applications, particularly for cell viability and anticancer activity against SiHa cancer cells where eutectic of benzanilide-salicylamide system infers its potential applicability for anticancer activity. © 2024